2009
DOI: 10.1002/uog.6282
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic prediction of macrosomia cannot be improved by combination with pregnancy‐specific characteristics

Abstract: respectively; P < 0.0005), whereas the performance of the Nahum and Stanislaw equation was similar but not superior to ultrasound alone (AUC 0.895, respectively; P > 0.05

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…Nahum and Stanislaw [54] and similarly Mazouni et al [55] combined sonographic data with maternal and pregnancy-specific variables such as gestational age, parity, fetal sex, maternal height and weight to increase the detection rate of macrosomic fetuses. Both studies showed some improvement but in a recent independent study these results were not confirmed [56] .…”
Section: Discussionmentioning
confidence: 64%
“…Nahum and Stanislaw [54] and similarly Mazouni et al [55] combined sonographic data with maternal and pregnancy-specific variables such as gestational age, parity, fetal sex, maternal height and weight to increase the detection rate of macrosomic fetuses. Both studies showed some improvement but in a recent independent study these results were not confirmed [56] .…”
Section: Discussionmentioning
confidence: 64%
“…Another option, especially for heavier infants, is an optimisation of the weight estimation through a combination of ultrasound findings with maternal and pregnancy-specific parameters such as gestational age, parity, gender of the foetus, and maternal height or weight. The presumed benefit of such an elaborate procedure is, however, a subject of controversial discussion in the current literature [45][46][47]. Nevertheless, there is consensus that maternal obesity increases the estimation errors [48,49].…”
mentioning
confidence: 99%
“…Despite the poor performance of weight estimation formulas in macrosomic fetuses in general [13, 25], estimating fetal weight is an essential part of everyday routine work in an obstetric department in the effort to detect infants who are at risk. Suspected macrosomia always alters the approach to a pregnancy in relation to possible perinatal risks and unwanted effects [26].…”
Section: Discussionmentioning
confidence: 99%